8. SURVEY OF DEPRESSION IN MALE INFERTILITY PATIENTS AT ANDROLOGY CENTER, VIET DUC UNIVERSITY HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2024)
In Vietnam, male infertility become a common issue and is documented to be associated with psychological problems. However, social constraints prevent a comprehensive understanding of this relationship. Our study aimed to investigate factors related to depression severity in people with male infertility. From July 2022 to December 2022, a direct survey was conducted at the Andrology Center of Viet Duc University Hospital, with 103 patients diagnosed with male infertility. The survey had questions including general information about the patient, and the depression symptom screening and monitoring scale (PHQ-9). The study found that the average age of the participants was 37.63 (11.84) years, with a male infertility rate of 17.69%. Some factors were related to depression in infertility patients such as education level and the subject’s role in the family. Our findings showed that the likelihood of depression occurring was higher in people with low education levels and holding roles such as: family head, eldest son, only child... These findings contribute to highlight the importance of considering mental health during caring for male infertility patients.
Keywords: Depression, anxiety, male infertility.